A burning problem: cannabis lessons learned from Colorado. (2nd January 2018) - Parnes, Jamie E.; Bravo, Adrian J.; Conner, Bradley T.; Pearson, Matthew R.
Abstract: With recent increases in cannabis' popularity, including being legalized in several states, new issues have emerged related to use. Increases in the number of users, new products, and home growing all present distinct concerns. In the present review, we explored various cannabis-related concerns (i.e. use, acquiring, growing, and public health/policy) that have arisen in Colorado in order to provide information on emerging issues and future directions to mitigate negative outcomes that could occur in states considering, or that already have implemented, a legalized cannabis market. Specific to Colorado, issues have arisen related to edibles, vaporizers/'e-cannabis', concentrates, growing, quantifying use, intoxicated driving, and arrests. Understanding cannabis dosing (including dose-dependent effects and related consequences), standardizing quantities, evaluating the safety of new products, and developing harm reduction interventions are important next steps for informing public policy and promoting health and well-being. Overall, increasing our knowledge of emerging issues related to cannabis is key to promoting the benefits and combating the potential harms of cannabis, especially for states legalizing medical or recreational cannabis.